Lightweight high-strength fabricated building board and preparation method thereof

By using raw materials such as polyvinyl chloride and modified fillers, combined with specific process treatment, lightweight and high strength prefabricated building boards are prepared, which solves the problems of insufficient strength and high production costs of existing PVC boards, and achieves higher strength and heat resistance, which is suitable for applications at higher temperatures.

CN119875263APending Publication Date: 2025-04-25JIANGXI ZHONGWEI CONSTR GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510022725.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing PVC construction panels have high production costs, insufficient strength, and easy cracking in construction, resulting in fewer reuses, limiting their application areas.

Method used

Lightweight high-strength prefabricated building panels are prepared through specific mixing and refining processes using polyvinyl chloride, modified fillers, dioctyl terephthalate, Ca/Zn stabilizers, polyethylene wax and calcium stearate as raw materials. The preparation method of the modified filler includes multi-step chemical reactions and treatments to improve the crosslinking and compatibility of nanosilica particles with polyvinyl chloride.

Benefits of technology

It improves the strength and heat resistance of building panels, extends the durability of the panels, reduces the stress damage rate during assembly and use, and makes the panels suitable for higher temperature applications.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a light-weight high-strength fabricated building board which comprises the following raw materials in parts by weight: 100 parts of polyvinyl chloride, 10-20 parts of modified filler, 10-20 parts of dioctyl terephthalate, 10-20 parts of heat stabilizer, 10-20 parts of polyethylene wax and 10-20 parts of calcium stearate. 20-30 parts of a modified filler; 15 to 18 parts of dioctyl terephthalate; 3-4 parts of a heat stabilizer; 2-3 parts of polyethylene wax; and 0.2 to 0.4 part of calcium stearate. The building board prepared through the method has high strength and heat resistance, the durability of the board is improved, the stress damage rate in the assembling and using process is reduced, meanwhile, the weather resistance of the polyvinyl chloride board is optimized, and the building board is suitable for application occasions with the relatively high temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyvinyl chloride building materials, and in particular to a lightweight and high-strength assembled building board and a preparation method thereof. Background Art

[0002] Plastic building boards can be used for more than 150 times and can be recycled. They have a wide temperature adaptability range, strong adaptability to specifications, can be sawed and drilled, and are easy to use. The flatness and smoothness of the board surface exceed the technical requirements of existing plain concrete boards. They have the functions of flame retardancy, corrosion resistance, water resistance and chemical corrosion resistance, and have good mechanical properties and electrical insulation properties. They can meet the requirements of various rectangular, cube, L-shaped and U-shaped building formwork. PVC building board is a plastic building board made of polyvinyl chloride as the main raw material. It has the characteristics of light weight, corrosion resistance and flame retardancy, so it is widely used in architectural decoration. However, the existing PVC building boards still have the disadvantages of high production cost, insufficient strength, easy cracking during construction, and few reuse times, which limits their application areas. Summary of the invention

[0003] To this end, the present invention provides a lightweight and high-strength assembled building board, the raw materials of which include polyvinyl chloride, modified filler, dioctyl terephthalate, Ca / Zn stabilizer, polyethylene wax and calcium stearate, wherein the preparation method of the modified filler is:

[0004] (1) preparing a mixture of hexadecyltrimethylammonium bromide, ethanol and water, stirring the mixture, adding γ-glycidyloxypropyltrimethoxysilane to the mixture under stirring, continuing stirring for more than 10 minutes after the addition is completed, heating in a water bath to 55±3° C. for insulation, then adding ethyl orthosilicate under stirring, continuing stirring for more than 30 minutes after the addition is completed, and then adding ammonia water, stirring at a constant temperature of 55±3° C. for more than 20 hours after the addition is completed, separating the solid from the liquid, washing the solid phase with ethanol for more than 2 times, then washing with deionized water for more than 2 times, drying, immersing the dried solid phase in hydrogen peroxide kept at 50±5° C., stirring for more than 3 hours, condensing and refluxing during the insulation process, separating the solid from the liquid after the insulation and stirring, washing the solid phase with deionized water for more than 3 times, drying, and obtaining a solid phase powder;

[0005] (2) preparing a composite ethanol solution of phosphoric acid and triethyl phosphate; heating the composite ethanol solution of phosphoric acid and triethyl phosphate to 50±3° C. in a water bath, then adding chitosan and the solid phase powder to the solution under stirring, and continuing to stir the solution at 50±3° C. for more than 30 hours after the addition is completed. After the insulation is completed, the solid and liquid are separated, and the solid phase is washed with a dilute acetic acid aqueous solution for more than 3 times, and then washed with deionized water for more than 3 times, and dried to obtain a primary modified powder;

[0006] (3) preparing a mixed solution of α-methylpyridine and dimethyl sulfoxide, adding the primary modified powder to the mixed solution of α-methylpyridine and dimethyl sulfoxide, stirring for more than 20 minutes, then adding methyl methacrylate and azobisisobutyronitrile under stirring, heating in a water bath to 60±3° C. after the addition is completed, stirring at this temperature for more than 5 hours, then separating the solid from the liquid, washing the solid phase with ethanol for more than 3 times, and drying to obtain the modified filler.

[0007] Furthermore, the raw materials are calculated by weight as follows: 100 parts of polyvinyl chloride; 20-30 parts of modified filler; 15-18 parts of dioctyl terephthalate; 3-4 parts of Ca / Zn stabilizer; 2-3 parts of polyethylene wax; and 0.2-0.4 parts of calcium stearate.

[0008] Furthermore, in the step (1), the mixing ratio of the hexadecyltrimethylammonium bromide, ethanol and water is hexadecyltrimethylammonium bromide: ethanol: water = 0.3-0.4 g: 60-70 mL: 100 mL; the added amount of the γ-glycidyloxypropyltrimethoxysilane, tetraethyl orthosilicate and ammonia water and the amount of the mixture added thereto is γ-glycidyloxypropyltrimethoxysilane: tetraethyl orthosilicate: ammonia water: mixture = 0.5-0.6 g: 1.5-2 g: 2-3 mL: 150 mL; the mass percentage of the solute in the ammonia water is 20%.

[0009] Furthermore, in the step (1), the mass percentage of the solute in the hydrogen peroxide is 10% to 20%, and the mass ratio of the dried solid phase immersed in the hydrogen peroxide is solid phase / hydrogen peroxide = 1g: 50 to 100g.

[0010] Furthermore, in the step (2), the composite ethanol solution of phosphoric acid and triethyl phosphate is mixed in a mass ratio of phosphoric acid: triethyl phosphate: ethanol = 1:1:6-7; chitosan and the solid phase powder are added to the composite ethanol solution of phosphoric acid and triethyl phosphate in a mass ratio of composite ethanol solution of phosphoric acid and triethyl phosphate: chitosan: solid phase powder = 50:3-4:1; the mass percentage of the solute in the dilute acetic acid aqueous solution is 2%-5%, and the solvent is water.

[0011] Furthermore, in the step (3), the mixed solution of α-picoline and dimethyl sulfoxide is prepared by mixing α-picoline and dimethyl sulfoxide in a mass ratio of α-picoline: dimethyl sulfoxide = 1 to 2:1, and the mass ratio of the primary modified powder, methyl methacrylate and azobisisobutyronitrile added to the mixed solution of α-picoline and dimethyl sulfoxide is primary modified powder: methyl methacrylate: azobisisobutyronitrile: mixed solution of α-picoline and dimethyl sulfoxide = 3 to 5: 0.4 to 0.8: 0.005 to 0.006: 100.

[0012] The present invention also discloses a method for preparing the above-mentioned lightweight and high-strength prefabricated building board, the steps comprising: weighing each raw material according to the said weight proportion, mixing each raw material evenly in a high-speed mixer, internally kneading and melt-blending the mixture in an internal mixer, extruding, injection molding the extruded pellets in a mold, cutting, and obtaining the said prefabricated building board.

[0013] Furthermore, the mixing temperature in the high-speed mixer is 100-110° C., and the mixing time is 10-15 min; the banburying melt blending temperature is 170-175° C., and the banburying time is 5 min.

[0014] Furthermore, the extrusion temperature sections are 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, and 175°C, the main machine speed is 18-20r / min, the melt pressure is 14-18MPa, and the injection molding temperature is 170-180°C.

[0015] The beneficial effects of the present invention are: the building board prepared by the method of the present invention has high strength and heat resistance, improves the durability of the board, reduces the stress damage rate during assembly and use, and optimizes the weather resistance of the polyvinyl chloride material board, so that the building board is suitable for applications with relatively high temperatures. The present invention first prepares nano-silica particles containing octadecylamine groups on the surface, improves the crosslinking degree and bonding force between the nano-silica particle filler and the polyvinyl chloride matrix, and can also reduce the agglomeration of the filler particles. Subsequently, chitosan phosphate is coated on the surface of the particles, which can further improve the compatibility of the filler with polyvinyl chloride, reduce the porosity between the filler and the matrix, and is conducive to increasing the overall strength of the material. Finally, by grafting a polymethyl methacrylate macromolecular structure on the filler surface, the active sites on the polymethyl methacrylate chain are bonded with the active sites on the polyvinyl chloride carbon chain and the carbon chain is entangled, which improves the connection and heat resistance of the two-phase interface area, thereby improving the strength and heat resistance of the building board as a whole. DETAILED DESCRIPTION

[0016] The present invention will be further described below in conjunction with the embodiments.

[0017] Example 1

[0018] A lightweight and high-strength assembled building board, the raw materials include polyvinyl chloride (model SG-5), modified filler, dioctyl terephthalate, Ca / Zn stabilizer, polyethylene wax and calcium stearate, and the weight proportion of each of the raw materials is: 100 parts of polyvinyl chloride; 20 parts of modified filler; 15 parts of dioctyl terephthalate; 3 parts of Ca / Zn stabilizer; 2 parts of polyethylene wax; 0.2 parts of calcium stearate. The preparation method of the modified filler is:

[0019] (1) preparing a mixture of hexadecyltrimethylammonium bromide, ethanol and water, wherein the mixing ratio of hexadecyltrimethylammonium bromide, ethanol and water is hexadecyltrimethylammonium bromide: ethanol: water = 0.3 g: 60 mL: 100 mL; stirring the mixture, adding γ-glycidyloxypropyltrimethoxysilane to the mixture under stirring, continuing stirring for 10 minutes after the addition is completed, heating in a water bath to 55° C. for insulation, then adding tetraethyl orthosilicate under stirring, continuing stirring for 30 minutes after the addition is completed, and then adding ammonia water, wherein the amount ratio of the γ-glycidyloxypropyltrimethoxysilane, tetraethyl orthosilicate and ammonia water to the mixture added thereto is: Oxypropyltrimethoxysilane:ethyl orthosilicate:ammonia water:mixture=0.5g:1.5g:2mL:150mL; the mass percentage of the solute in the ammonia water is 20%; after the addition is completed, stir at a constant temperature of 55°C for 20h, separate the solid and liquid, wash the solid phase with ethanol twice, wash it with deionized water twice, dry it at 60°C for 6h, soak the dried solid phase in hydrogen peroxide kept at 50°C, the mass percentage of the solute in the hydrogen peroxide is 10%, and the mass ratio of the dried solid phase soaked in hydrogen peroxide is solid phase / hydrogen peroxide=1g:50g; stir for 3h, condense and reflux during the insulation process, separate the solid and liquid after the insulation and stirring, wash the solid phase with deionized water 3 times, and dry it at 60°C for 4h to obtain a solid phase powder;

[0020] (2) preparing a composite ethanol solution of phosphoric acid and triethyl phosphate; the composite ethanol solution of phosphoric acid and triethyl phosphate is mixed in a mass ratio of phosphoric acid: triethyl phosphate: ethanol = 1:1:6; heating the composite ethanol solution of phosphoric acid and triethyl phosphate to 50°C in a water bath, then adding chitosan and the solid phase powder to the solution under stirring, adding chitosan and the solid phase powder to the composite ethanol solution of phosphoric acid and triethyl phosphate in a mass ratio of phosphoric acid and triethyl phosphate composite ethanol solution: chitosan: solid phase powder = 50:3:1; continuing to stir the solution at 50°C for 30 hours after the addition is completed, separating the solid and the liquid after the insulation is completed, washing the solid phase with a dilute acetic acid aqueous solution for 3 times, wherein the mass percentage of the solute in the dilute acetic acid aqueous solution is 2%, and the solvent is water; washing it with deionized water for 3 times, and drying it at 60°C for 4 hours to obtain a primary modified powder;

[0021] (3) preparing a mixed solution of α-methylpyridine and dimethyl sulfoxide, wherein the mixed solution of α-methylpyridine and dimethyl sulfoxide is prepared by mixing α-methylpyridine and dimethyl sulfoxide in a mass ratio of α-methylpyridine: dimethyl sulfoxide = 1:1, adding the primary modified powder to the mixed solution of α-methylpyridine and dimethyl sulfoxide, stirring for 20 minutes, and then adding methyl methacrylate and azobisisobutyronitrile under stirring, wherein the mass ratio of the primary modified powder, methyl methacrylate and azobisisobutyronitrile added to the mixed solution of α-methylpyridine and dimethyl sulfoxide is primary modified powder: methyl methacrylate: azobisisobutyronitrile: mixed solution of α-methylpyridine and dimethyl sulfoxide = 3:0.4:0.005:100; after the addition is completed, heating in a water bath to 60° C., stirring at this temperature for 5 hours, and then separating the solid and liquid, washing the solid phase with ethanol for 3 times, and drying at 60° C. for 4 hours to obtain the modified filler.

[0022] The preparation method of the above-mentioned lightweight and high-strength prefabricated building board comprises the following steps: weighing each raw material according to the said weight proportion, mixing each raw material evenly in a high-speed mixer, the mixing temperature in the high-speed mixer is 105°C, and the mixing time is 10 minutes; the mixed materials are melt-mixed in an internal mixer, the internal mixing melt-mixing temperature is 170°C, and the internal mixing time is 5 minutes; extrusion, the extruded pellets are injection molded in a mold, the extrusion temperature sections are 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, and 175°C respectively, the main engine speed is 18r / min, the melt pressure is 15MPa, and the injection molding temperature is 175°C; cutting to obtain the said prefabricated building board.

[0023] Example 2

[0024] A lightweight and high-strength assembled building board, the raw materials include polyvinyl chloride (model SG-5), modified filler, dioctyl terephthalate, Ca / Zn stabilizer, polyethylene wax and calcium stearate, and the weight proportion of each of the raw materials is: 100 parts of polyvinyl chloride; 25 parts of modified filler; 16 parts of dioctyl terephthalate; 3 parts of Ca / Zn stabilizer; 2 parts of polyethylene wax; 0.3 parts of calcium stearate. The preparation method of the modified filler is:

[0025] (1) preparing a mixture of hexadecyltrimethylammonium bromide, ethanol and water, wherein the mixing ratio of hexadecyltrimethylammonium bromide, ethanol and water is hexadecyltrimethylammonium bromide: ethanol: water = 0.3 g: 65 mL: 100 mL; stirring the mixture, adding γ-glycidyloxypropyltrimethoxysilane to the mixture under stirring, continuing stirring for 10 minutes after the addition is completed, heating in a water bath to 55° C. for insulation, then adding tetraethyl orthosilicate under stirring, continuing stirring for 30 minutes after the addition is completed, and then adding ammonia water, wherein the amount ratio of the γ-glycidyloxypropyltrimethoxysilane, tetraethyl orthosilicate and ammonia water to the mixture added thereto is: Oxypropyltrimethoxysilane:ethyl orthosilicate:ammonia water:mixture=0.5g:1.5g:2mL:150mL; the mass percentage of the solute in the ammonia water is 20%; after the addition is completed, stir at a constant temperature of 55°C for 20h, separate the solid and liquid, wash the solid phase with ethanol twice, wash it with deionized water twice, dry it at 60°C for 6h, soak the dried solid phase in hydrogen peroxide kept at 50°C, the mass percentage of the solute in the hydrogen peroxide is 10%, and the mass ratio of the dried solid phase soaked in hydrogen peroxide is solid phase / hydrogen peroxide=1g:50g; stir for 3h, condense and reflux during the insulation process, separate the solid and liquid after the insulation and stirring, wash the solid phase with deionized water 3 times, and dry it at 60°C for 4h to obtain a solid phase powder;

[0026] (2) preparing a composite ethanol solution of phosphoric acid and triethyl phosphate; the composite ethanol solution of phosphoric acid and triethyl phosphate is mixed in a mass ratio of phosphoric acid: triethyl phosphate: ethanol = 1:1:6; heating the composite ethanol solution of phosphoric acid and triethyl phosphate to 50°C in a water bath, then adding chitosan and the solid phase powder to the solution under stirring, adding chitosan and the solid phase powder to the composite ethanol solution of phosphoric acid and triethyl phosphate in a mass ratio of phosphoric acid and triethyl phosphate composite ethanol solution: chitosan: solid phase powder = 50:3:1; continuing to stir the solution at 50°C for 30 hours after the addition is completed, separating the solid and the liquid after the insulation is completed, washing the solid phase with a dilute acetic acid aqueous solution for 3 times, wherein the mass percentage of the solute in the dilute acetic acid aqueous solution is 2%, and the solvent is water; washing it with deionized water for 3 times, and drying it at 60°C for 4 hours to obtain a primary modified powder;

[0027] (3) preparing a mixed solution of α-methylpyridine and dimethyl sulfoxide, wherein the mixed solution of α-methylpyridine and dimethyl sulfoxide is prepared by mixing α-methylpyridine and dimethyl sulfoxide in a mass ratio of α-methylpyridine: dimethyl sulfoxide = 1:1, adding the primary modified powder to the mixed solution of α-methylpyridine and dimethyl sulfoxide, stirring for 20 minutes, and then adding methyl methacrylate and azobisisobutyronitrile under stirring, wherein the mass ratio of the primary modified powder, methyl methacrylate and azobisisobutyronitrile added to the mixed solution of α-methylpyridine and dimethyl sulfoxide is primary modified powder: methyl methacrylate: azobisisobutyronitrile: mixed solution of α-methylpyridine and dimethyl sulfoxide = 4:0.6:0.005:100; after the addition is completed, heating in a water bath to 60° C., stirring at this temperature for 5 hours, and then separating the solid and liquid, washing the solid phase with ethanol for 3 times, and drying at 60° C. for 4 hours to obtain the modified filler.

[0028] The preparation method of the above-mentioned lightweight and high-strength prefabricated building board comprises the following steps: weighing each raw material according to the said weight proportion, mixing each raw material evenly in a high-speed mixer, the mixing temperature in the high-speed mixer is 105°C, and the mixing time is 10 minutes; the mixed materials are melt-mixed in an internal mixer, the internal mixing melt-mixing temperature is 170°C, and the internal mixing time is 5 minutes; extrusion, the extruded pellets are injection molded in a mold, the extrusion temperature sections are 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, and 175°C respectively, the main engine speed is 18r / min, the melt pressure is 15MPa, and the injection molding temperature is 175°C; cutting to obtain the said prefabricated building board.

[0029] Example 3

[0030] A lightweight and high-strength assembled building board, the raw materials include polyvinyl chloride (model SG-5), modified filler, dioctyl terephthalate, Ca / Zn stabilizer, polyethylene wax and calcium stearate, and the weight proportion of each of the raw materials is: 100 parts of polyvinyl chloride; 25 parts of modified filler; 17 parts of dioctyl terephthalate; 4 parts of Ca / Zn stabilizer; 3 parts of polyethylene wax; 0.3 parts of calcium stearate. The preparation method of the modified filler is:

[0031] (1) preparing a mixture of hexadecyltrimethylammonium bromide, ethanol and water, wherein the mixing ratio of hexadecyltrimethylammonium bromide, ethanol and water is hexadecyltrimethylammonium bromide: ethanol: water = 0.4 g: 65 mL: 100 mL; stirring the mixture, adding γ-glycidyloxypropyltrimethoxysilane to the mixture under stirring, continuing stirring for 10 minutes after the addition is completed, heating in a water bath to 55° C. for insulation, then adding tetraethyl orthosilicate under stirring, continuing stirring for 30 minutes after the addition is completed, and then adding ammonia water, wherein the amount of γ-glycidyloxypropyltrimethoxysilane, tetraethyl orthosilicate and ammonia water added to the mixture is 0.4 g: 65 mL: 100 mL; Etheroxypropyl trimethoxysilane: ethyl orthosilicate: ammonia water: mixture = 0.6g: 2g: 3mL: 150mL; the mass percentage of the solute in the ammonia water is 20%; after the addition is completed, stir at a constant temperature of 55°C for 20h, separate the solid and liquid, wash the solid phase with ethanol twice, wash it with deionized water twice, dry it at 60°C for 6h, soak the dried solid phase in hydrogen peroxide kept at 50°C, the mass percentage of the solute in the hydrogen peroxide is 10%, and the mass ratio of the dried solid phase soaked in hydrogen peroxide is solid phase / hydrogen peroxide = 1g: 50g; stir for 3h, condense and reflux during the insulation process, separate the solid and liquid after the insulation and stirring, wash the solid phase with deionized water 3 times, and dry it at 60°C for 4h to obtain a solid phase powder;

[0032] (2) preparing a composite ethanol solution of phosphoric acid and triethyl phosphate; the composite ethanol solution of phosphoric acid and triethyl phosphate is mixed in a mass ratio of phosphoric acid: triethyl phosphate: ethanol = 1:1:7; heating the composite ethanol solution of phosphoric acid and triethyl phosphate to 50° C. in a water bath, then adding chitosan and the solid phase powder to the solution under stirring, adding chitosan and the solid phase powder to the composite ethanol solution of phosphoric acid and triethyl phosphate in a mass ratio of phosphoric acid and triethyl phosphate composite ethanol solution: chitosan: solid phase powder = 50:4:1; continuing to stir the solution at 50° C. for 30 hours after the addition is completed, separating the solid and the liquid after the insulation is completed, washing the solid phase with a dilute acetic acid aqueous solution for 3 times, wherein the mass percentage of the solute in the dilute acetic acid aqueous solution is 2%, and the solvent is water; then washing with deionized water for 3 times, drying at 60° C. for 4 hours, and obtaining a primary modified powder;

[0033] (3) preparing a mixed solution of α-methylpyridine and dimethyl sulfoxide, wherein the mixed solution of α-methylpyridine and dimethyl sulfoxide is prepared by mixing α-methylpyridine and dimethyl sulfoxide in a mass ratio of α-methylpyridine: dimethyl sulfoxide = 2:1, adding the primary modified powder to the mixed solution of α-methylpyridine and dimethyl sulfoxide, stirring for 20 minutes, and then adding methyl methacrylate and azobisisobutyronitrile under stirring, wherein the mass ratio of the primary modified powder, methyl methacrylate and azobisisobutyronitrile added to the mixed solution of α-methylpyridine and dimethyl sulfoxide is primary modified powder: methyl methacrylate: azobisisobutyronitrile: mixed solution of α-methylpyridine and dimethyl sulfoxide = 4:0.6:0.006:100; after the addition is completed, heating in a water bath to 60° C., stirring at this temperature for 5 hours, and then separating the solid and liquid, washing the solid phase with ethanol for 3 times, and drying at 60° C. for 4 hours to obtain the modified filler.

[0034] The preparation method of the above-mentioned lightweight and high-strength prefabricated building board comprises the following steps: weighing each raw material according to the said weight proportion, mixing each raw material evenly in a high-speed mixer, the mixing temperature in the high-speed mixer is 105°C, and the mixing time is 10 minutes; the mixed materials are melt-mixed in an internal mixer, the internal mixing melt-mixing temperature is 170°C, and the internal mixing time is 5 minutes; extrusion, the extruded pellets are injection molded in a mold, the extrusion temperature sections are 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, and 175°C respectively, the main engine speed is 18r / min, the melt pressure is 15MPa, and the injection molding temperature is 175°C; cutting to obtain the said prefabricated building board.

[0035] Example 4

[0036] A lightweight and high-strength assembled building board, the raw materials include polyvinyl chloride (model SG-5), modified filler, dioctyl terephthalate, Ca / Zn stabilizer, polyethylene wax and calcium stearate, and the weight proportion of each of the raw materials is: 100 parts of polyvinyl chloride; 30 parts of modified filler; 18 parts of dioctyl terephthalate; 4 parts of Ca / Zn stabilizer; 3 parts of polyethylene wax; 0.4 parts of calcium stearate. The preparation method of the modified filler is:

[0037] (1) preparing a mixture of hexadecyltrimethylammonium bromide, ethanol and water, wherein the mixing ratio of the hexadecyltrimethylammonium bromide, ethanol and water is hexadecyltrimethylammonium bromide: ethanol: water = 0.4 g: 70 mL: 100 mL; stirring the mixture, adding γ-glycidyloxypropyltrimethoxysilane to the mixture under stirring, continuing stirring for 10 minutes after the addition is completed, heating in a water bath to 55° C. for insulation, then adding tetraethyl orthosilicate under stirring, continuing stirring for 30 minutes after the addition is completed, and then adding ammonia water, wherein the amount of the γ-glycidyloxypropyltrimethoxysilane, tetraethyl orthosilicate and ammonia water added to the mixture is 0.4 g: 70 mL: 100 mL; stirring the mixture, and adding γ-glycidyloxypropyltrimethoxysilane to the mixture under stirring. Etheroxypropyl trimethoxysilane: ethyl orthosilicate: ammonia water: mixture = 0.6g: 2g: 3mL: 150mL; the mass percentage of the solute in the ammonia water is 20%; after the addition is completed, stir at a constant temperature of 55°C for 20h, separate the solid and liquid, wash the solid phase with ethanol twice, wash it with deionized water twice, dry it at 60°C for 6h, soak the dried solid phase in hydrogen peroxide kept at 50°C, the mass percentage of the solute in the hydrogen peroxide is 10%, and the mass ratio of the dried solid phase soaked in hydrogen peroxide is solid phase / hydrogen peroxide = 1g: 50g; stir for 3h, condense and reflux during the insulation process, separate the solid and liquid after the insulation and stirring, wash the solid phase with deionized water 3 times, and dry it at 60°C for 4h to obtain a solid phase powder;

[0038] (2) preparing a composite ethanol solution of phosphoric acid and triethyl phosphate; the composite ethanol solution of phosphoric acid and triethyl phosphate is mixed in a mass ratio of phosphoric acid: triethyl phosphate: ethanol = 1:1:7; heating the composite ethanol solution of phosphoric acid and triethyl phosphate to 50° C. in a water bath, then adding chitosan and the solid phase powder to the solution under stirring, adding chitosan and the solid phase powder to the composite ethanol solution of phosphoric acid and triethyl phosphate in a mass ratio of phosphoric acid and triethyl phosphate composite ethanol solution: chitosan: solid phase powder = 50:4:1; continuing to stir the solution at 50° C. for 30 hours after the addition is completed, separating the solid and the liquid after the insulation is completed, washing the solid phase with a dilute acetic acid aqueous solution for 3 times, wherein the mass percentage of the solute in the dilute acetic acid aqueous solution is 2%, and the solvent is water; then washing with deionized water for 3 times, drying at 60° C. for 4 hours, and obtaining a primary modified powder;

[0039] (3) preparing a mixed solution of α-methylpyridine and dimethyl sulfoxide, wherein the mixed solution of α-methylpyridine and dimethyl sulfoxide is prepared by mixing α-methylpyridine and dimethyl sulfoxide in a mass ratio of α-methylpyridine: dimethyl sulfoxide = 2:1, adding the primary modified powder to the mixed solution of α-methylpyridine and dimethyl sulfoxide, stirring for 20 minutes, and then adding methyl methacrylate and azobisisobutyronitrile under stirring, wherein the mass ratio of the primary modified powder, methyl methacrylate and azobisisobutyronitrile added to the mixed solution of α-methylpyridine and dimethyl sulfoxide is primary modified powder: methyl methacrylate: azobisisobutyronitrile: mixed solution of α-methylpyridine and dimethyl sulfoxide = 5:0.8:0.006:100; after the addition is completed, heating in a water bath to 60° C., stirring at this temperature for 5 hours, and then separating the solid and liquid, washing the solid phase with ethanol for 3 times, and drying at 60° C. for 4 hours to obtain the modified filler.

[0040] The preparation method of the above-mentioned lightweight and high-strength prefabricated building board comprises the following steps: weighing each raw material according to the said weight proportion, mixing each raw material evenly in a high-speed mixer, the mixing temperature in the high-speed mixer is 105°C, and the mixing time is 10 minutes; the mixed materials are melt-mixed in an internal mixer, the internal mixing melt-mixing temperature is 170°C, and the internal mixing time is 5 minutes; extrusion, the extruded pellets are injection molded in a mold, the extrusion temperature sections are 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, and 175°C respectively, the main engine speed is 18r / min, the melt pressure is 15MPa, and the injection molding temperature is 175°C; cutting to obtain the said prefabricated building board.

[0041] Comparative Example 1

[0042] A comparative building board material includes polyvinyl chloride (model SG-5), modified filler, dioctyl terephthalate, Ca / Zn stabilizer, polyethylene wax and calcium stearate, wherein the weight proportion of each of the raw materials is as follows: 100 parts of polyvinyl chloride; 25 parts of modified filler; 16 parts of dioctyl terephthalate; 3 parts of Ca / Zn stabilizer; 2 parts of polyethylene wax; and 0.3 parts of calcium stearate. The preparation method of the modified filler is as follows:

[0043] (1) preparing a mixture of hexadecyltrimethylammonium bromide, ethanol and water, wherein the mixing ratio of hexadecyltrimethylammonium bromide, ethanol and water is hexadecyltrimethylammonium bromide: ethanol: water = 0.3 g: 65 mL: 100 mL; stirring the mixture, adding γ-glycidyloxypropyltrimethoxysilane to the mixture under stirring, continuing stirring for 10 minutes after the addition is completed, heating in a water bath to 55° C. for insulation, then adding tetraethyl orthosilicate under stirring, continuing stirring for 30 minutes after the addition is completed, and then adding ammonia water, wherein the amount ratio of the γ-glycidyloxypropyltrimethoxysilane, tetraethyl orthosilicate and ammonia water to the mixture added thereto is: Oxypropyltrimethoxysilane:ethyl orthosilicate:ammonia water:mixture=0.5g:1.5g:2mL:150mL; the mass percentage of the solute in the ammonia water is 20%; after the addition is completed, stir at a constant temperature of 55°C for 20h, separate the solid and liquid, wash the solid phase with ethanol twice, wash it with deionized water twice, dry it at 60°C for 6h, soak the dried solid phase in hydrogen peroxide kept at 50°C, the mass percentage of the solute in the hydrogen peroxide is 10%, and the mass ratio of the dried solid phase soaked in hydrogen peroxide is solid phase / hydrogen peroxide=1g:50g; stir for 3h, condense and reflux during the insulation process, separate the solid and liquid after the insulation and stirring, wash the solid phase with deionized water 3 times, and dry it at 60°C for 4h to obtain a solid phase powder;

[0044] (2) preparing a mixed solution of α-picoline and dimethyl sulfoxide, wherein the mixed solution of α-picoline and dimethyl sulfoxide is prepared by mixing α-picoline and dimethyl sulfoxide in a mass ratio of α-picoline: dimethyl sulfoxide = 1:1, adding the solid phase powder to the mixed solution of α-picoline and dimethyl sulfoxide, stirring for 20 minutes, and then adding methyl methacrylate and azobisisobutyronitrile under stirring, wherein the mass ratio of the solid phase powder, methyl methacrylate and azobisisobutyronitrile added to the mixed solution of α-picoline and dimethyl sulfoxide is solid phase powder: methyl methacrylate: azobisisobutyronitrile: mixed solution of α-picoline and dimethyl sulfoxide = 4:0.6:0.005:100; after the addition is completed, heating in a water bath to 60° C., stirring at this temperature for 5 hours, and then separating the solid and liquid, washing the solid phase with ethanol for 3 times, and drying at 60° C. for 4 hours to obtain the modified filler.

[0045] The preparation method of the above-mentioned lightweight and high-strength prefabricated building board comprises the following steps: weighing each raw material according to the said weight proportion, mixing each raw material evenly in a high-speed mixer, the mixing temperature in the high-speed mixer is 105°C, and the mixing time is 10 minutes; the mixed materials are melt-mixed in an internal mixer, the internal mixing melt-mixing temperature is 170°C, and the internal mixing time is 5 minutes; extrusion, the extruded pellets are injection molded in a mold, the extrusion temperature sections are 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, and 175°C respectively, the main engine speed is 18r / min, the melt pressure is 15MPa, and the injection molding temperature is 175°C; cutting to obtain the said prefabricated building board.

[0046] Comparative Example 2

[0047] A comparative building board material includes polyvinyl chloride (model SG-5), modified filler, dioctyl terephthalate, Ca / Zn stabilizer, polyethylene wax and calcium stearate, wherein the weight proportion of each of the raw materials is as follows: 100 parts of polyvinyl chloride; 25 parts of modified filler; 16 parts of dioctyl terephthalate; 3 parts of Ca / Zn stabilizer; 2 parts of polyethylene wax; and 0.3 parts of calcium stearate. The preparation method of the modified filler is as follows:

[0048] (1) preparing a mixture of hexadecyltrimethylammonium bromide, ethanol and water, wherein the mixing ratio of hexadecyltrimethylammonium bromide, ethanol and water is hexadecyltrimethylammonium bromide: ethanol: water = 0.3 g: 65 mL: 100 mL; stirring the mixture, adding γ-glycidyloxypropyltrimethoxysilane to the mixture under stirring, continuing stirring for 10 minutes after the addition is completed, heating in a water bath to 55° C. for insulation, then adding tetraethyl orthosilicate under stirring, continuing stirring for 30 minutes after the addition is completed, and then adding ammonia water, wherein the amount ratio of the γ-glycidyloxypropyltrimethoxysilane, tetraethyl orthosilicate and ammonia water to the mixture added thereto is: Oxypropyltrimethoxysilane:ethyl orthosilicate:ammonia water:mixture=0.5g:1.5g:2mL:150mL; the mass percentage of the solute in the ammonia water is 20%; after the addition is completed, stir at a constant temperature of 55°C for 20h, separate the solid and liquid, wash the solid phase with ethanol twice, wash it with deionized water twice, dry it at 60°C for 6h, soak the dried solid phase in hydrogen peroxide kept at 50°C, the mass percentage of the solute in the hydrogen peroxide is 10%, and the mass ratio of the dried solid phase soaked in hydrogen peroxide is solid phase / hydrogen peroxide=1g:50g; stir for 3h, condense and reflux during the insulation process, separate the solid and liquid after the insulation and stirring, wash the solid phase with deionized water 3 times, and dry it at 60°C for 4h to obtain a solid phase powder;

[0049] (2) preparing a composite ethanol solution of phosphoric acid and triethyl phosphate; the composite ethanol solution of phosphoric acid and triethyl phosphate is mixed in a mass ratio of phosphoric acid: triethyl phosphate: ethanol = 1:1:6; heating the composite ethanol solution of phosphoric acid and triethyl phosphate to 50°C in a water bath, and then adding chitosan and the solid phase powder to the solution under stirring, and adding chitosan and the solid phase powder to the composite ethanol solution of phosphoric acid and triethyl phosphate in a mass ratio of composite ethanol solution of phosphoric acid and triethyl phosphate: chitosan: solid phase powder = 50:3:1; continuing to stir the solution at 50°C for 30 hours after the addition is completed, separating the solid and the liquid after the insulation is completed, washing the solid phase with a dilute acetic acid aqueous solution for 3 times, wherein the mass percentage of the solute in the dilute acetic acid aqueous solution is 2%, and the solvent is water; then washing with deionized water for 3 times, and drying at 60°C for 4 hours to obtain the modified filler described in this comparative example.

[0050] The preparation method of the above-mentioned lightweight and high-strength prefabricated building board comprises the following steps: weighing each raw material according to the said weight proportion, mixing each raw material evenly in a high-speed mixer, the mixing temperature in the high-speed mixer is 105°C, and the mixing time is 10 minutes; the mixed materials are melt-mixed in an internal mixer, the internal mixing melt-mixing temperature is 170°C, and the internal mixing time is 5 minutes; extrusion, the extruded pellets are injection molded in a mold, the extrusion temperature sections are 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, and 175°C respectively, the main engine speed is 18r / min, the melt pressure is 15MPa, and the injection molding temperature is 175°C; cutting to obtain the said prefabricated building board.

[0051] Example 5

[0052] The tensile strength of the building boards prepared by the methods described in the above embodiments and comparative examples was tested according to the requirements of standard GB / T 1040.1-2018, and the tensile speed was set to 50 mm / min. The Vicat softening temperature of the building boards prepared by the methods described in the above embodiments and comparative examples was tested according to the requirements of standard GB / T1633-2000, and the heating rate was set to 50°C / h and the load was 5 kg. The results are shown in Table 1.

[0053] As shown in Table 1, the building board prepared by the method of the present invention has high strength and heat resistance, improves the durability of the board, reduces the stress damage rate during assembly and use, and optimizes the weather resistance of the polyvinyl chloride material board, so that the building board is suitable for applications with relatively high temperatures. The present invention first prepares nano-silica particles containing octadecylamine groups on the surface, improves the crosslinking degree and bonding force between the nano-silica particle filler and the polyvinyl chloride matrix, and can also reduce the agglomeration of the filler particles. Subsequently, chitosan phosphate is coated on the surface of the particles, which can further improve the compatibility of the filler with polyvinyl chloride, reduce the porosity between the filler and the matrix, and is conducive to increasing the overall strength of the material. Finally, by grafting the polymethyl methacrylate macromolecular structure on the filler surface, the active sites on the polymethyl methacrylate chain are bonded with the active sites on the polyvinyl chloride carbon chain and the carbon chain is entangled, which improves the connection and heat resistance of the two-phase interface area, thereby improving the strength and heat resistance of the building board as a whole.

[0054] Table 1

[0055] Experimental Group Tensile strength(MPa) Vicat softening temperature(℃) Example 1 39.6 90 Example 2 41.9 93 Example 3 41.5 93 Example 4 40.8 91 Comparative Example 1 29.1 85 Comparative Example 2 28.7 83

[0056] The technical solution provided by the present invention is introduced in detail above. For those skilled in the art, according to the concept of the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A lightweight and high-strength assembled building board, characterized in that: The raw materials include polyvinyl chloride, modified filler, dioctyl terephthalate, Ca / Zn stabilizer, polyethylene wax and calcium stearate, wherein the preparation method of the modified filler is: (1) preparing a mixture of hexadecyltrimethylammonium bromide, ethanol and water, stirring the mixture, adding γ-glycidyloxypropyltrimethoxysilane to the mixture under stirring, continuing stirring for more than 10 minutes after the addition is completed, heating in a water bath to 55±3° C. for insulation, then adding ethyl orthosilicate under stirring, continuing stirring for more than 30 minutes after the addition is completed, and then adding ammonia water, stirring at a constant temperature of 55±3° C. for more than 20 hours after the addition is completed, separating the solid from the liquid, washing the solid phase with ethanol for more than 2 times, then washing with deionized water for more than 2 times, drying, immersing the dried solid phase in hydrogen peroxide kept at 50±5° C., stirring for more than 3 hours, condensing and refluxing during the insulation process, separating the solid from the liquid after the insulation and stirring, washing the solid phase with deionized water for more than 3 times, drying, and obtaining a solid phase powder; (2) preparing a composite ethanol solution of phosphoric acid and triethyl phosphate; heating the composite ethanol solution of phosphoric acid and triethyl phosphate to 50±3° C. in a water bath, then adding chitosan and the solid phase powder to the solution under stirring, and continuing to stir the solution at 50±3° C. for more than 30 hours after the addition is completed. After the insulation is completed, the solid and liquid are separated, and the solid phase is washed with a dilute acetic acid aqueous solution for more than 3 times, and then washed with deionized water for more than 3 times, and dried to obtain a primary modified powder; (3) preparing a mixed solution of α-methylpyridine and dimethyl sulfoxide, adding the primary modified powder to the mixed solution of α-methylpyridine and dimethyl sulfoxide, stirring for more than 20 minutes, then adding methyl methacrylate and azobisisobutyronitrile under stirring, heating in a water bath to 60±3° C. after the addition is completed, stirring at this temperature for more than 5 hours, then separating the solid from the liquid, washing the solid phase with ethanol for more than 3 times, and drying to obtain the modified filler.

2. A lightweight and high-strength assembled building board according to claim 1, characterized in that: The raw materials are calculated by weight as follows: 100 parts of polyvinyl chloride; 20-30 parts of modified filler; 15-18 parts of dioctyl terephthalate; 3-4 parts of Ca / Zn stabilizer; 2-3 parts of polyethylene wax; and 0.2-0.4 parts of calcium stearate.

3. A lightweight and high-strength assembled building board according to claim 2, characterized in that: In the step (1), the mixing ratio of the hexadecyltrimethylammonium bromide, ethanol and water is hexadecyltrimethylammonium bromide: ethanol: water = 0.3-0.4 g: 60-70 mL: 100 mL; the added amount of the γ-glycidyloxypropyltrimethoxysilane, tetraethyl orthosilicate and ammonia water and the amount of the mixture added thereto is γ-glycidyloxypropyltrimethoxysilane: tetraethyl orthosilicate: ammonia water: mixture = 0.5-0.6 g: 1.5-2 g: 2-3 mL: 150 mL; the mass percentage of the solute in the ammonia water is 20%.

4. A lightweight and high-strength assembled building board according to claim 2, characterized in that: In the step (1), the mass percentage of the solute in the hydrogen peroxide is 10% to 20%, and the mass ratio of the dried solid phase immersed in the hydrogen peroxide is solid phase / hydrogen peroxide=1g:50 to 100g.

5. The lightweight and high-strength assembled building board according to claim 2, characterized in that: In the step (2), the composite ethanol solution of phosphoric acid and triethyl phosphate is mixed in a mass ratio of phosphoric acid: triethyl phosphate: ethanol = 1:1:6-7; chitosan and the solid phase powder are added to the composite ethanol solution of phosphoric acid and triethyl phosphate in a mass ratio of composite ethanol solution of phosphoric acid and triethyl phosphate: chitosan: solid phase powder = 50:3-4:1; the mass percentage of the solute in the dilute acetic acid aqueous solution is 2%-5%, and the solvent is water.

6. A lightweight and high-strength assembled building board according to claim 2, characterized in that: In the step (3), the mixed solution of α-picoline and dimethyl sulfoxide is prepared by mixing α-picoline and dimethyl sulfoxide in a mass ratio of α-picoline: dimethyl sulfoxide = 1 to 2:1, and the mass ratio of the primary modified powder, methyl methacrylate and azobisisobutyronitrile added to the mixed solution of α-picoline and dimethyl sulfoxide is primary modified powder: methyl methacrylate: azobisisobutyronitrile: mixed solution of α-picoline and dimethyl sulfoxide = 3 to 5: 0.4 to 0.8: 0.005 to 0.006:

100.

7. The method for preparing a lightweight and high-strength assembled building board according to claim 2, characterized in that the steps include: The raw materials are weighed according to the weight proportions, and the raw materials are uniformly mixed in a high-speed mixer. The mixed materials are melt-mixed in an internal mixer, extruded, and the extruded pellets are injection-molded in a mold and cut to obtain the assembled building board.

8. A preparation method according to claim 7, characterized in that: The mixing temperature in the high-speed mixer is 100-110° C., and the mixing time is 10-15 minutes; the banburying melt blending temperature is 170-175° C., and the banburying time is 5 minutes.

9. A preparation method according to claim 7, characterized in that: The extrusion temperature sections are 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, and 175°C, the main engine speed is 18-20r / min, the melt pressure is 14-18MPa, and the injection molding temperature is 170-180°C.